An ultralight aerogel-type urea absorbent for the development of a wearable artificial kidney. (23rd March 2023) - Yuan, Yaping; Li, Jing; Guo, Chenyuan; Zhang, Lili; Song, Yuyan; He, Yanli; Luo, Yankun; Shen, Shuguang
Abstract : Cellulose aerogel is used for urea adsorption for the first time, and displays a fast adsorption rate and high adsorption capacity. Abstract : Cellulose aerogels were synthesized to be used for urea adsorption and targeting a fast adsorption rate and high adsorption capacity. This kind of urea adsorbent was synthesized by a sol–gel method in a simple NaOH/urea aqueous solution system. The aerogels were characterized by FT-IR spectroscopy, XRD, SEM, and N2 adsorption/desorption techniques and their adsorption properties were evaluated. The results showed that the aerogels comprised an ultralight mesoporous material with a large specific surface area and a porous three-dimensional network structure. The adsorption process followed the Freundlich model and the pseudo-first-order kinetic model. The synthesized aerogels had a superior adsorption capacity and a fast adsorption rate, and adsorption equilibrium could be reached within 60 min under the human physiological temperature. Therefore, this aerogel type of absorbent has potential applications for the adsorption of urea in dialysate.